Measuring sustainable production (OECD sustainable development studies., 2008)
Promoting sustainable production and consumption is at the core of sustainable development, which depends on achieving long-term economic growth that is consistent with environmental and social needs. This volume reviews the state-of-the-art in measuring sustainable production processes in industry. It includes metrics developed by business, trade unions, academics, NGOs, and the OECD and IEA. These measurement approaches cover the "triple bottom line" (economic, environmental and social dimensions) of industrial sustainability.--Publisher's description.